2018
DOI: 10.1007/s12410-018-9441-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Cardiac Involvement in Chronic Kidney Disease Using CMR—a Systematic Review

Abstract: Purpose of ReviewThe aim of the review was to identify and describe recent advances (over the last 3 years) in cardiac magnetic resonance (CMR) imaging in patients with chronic kidney disease (CKD). We conducted a literature review in line with current guidelines.Recent FindingsThe authors identified 22 studies. Patients with CKD had left ventricular global and regional dysfunction and adverse remodeling. Stress testing with CMR revealed a reduced stress-response in CKD patients. Native T1 relaxation times (as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…To the best of our knowledge, our study is the largest observational prospective study using in-depth and comprehensive characterization of CVD in CKD, providing novel pathophysiological insights that might shed light to the excess of CVD in CKD [2]. Several previous studies reported on T1 mapping in the CKD patients, generally revealing significantly higher values compared to controls, which were reproducible and unaffected by the fluid status [27,28].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…To the best of our knowledge, our study is the largest observational prospective study using in-depth and comprehensive characterization of CVD in CKD, providing novel pathophysiological insights that might shed light to the excess of CVD in CKD [2]. Several previous studies reported on T1 mapping in the CKD patients, generally revealing significantly higher values compared to controls, which were reproducible and unaffected by the fluid status [27,28].…”
Section: Discussionmentioning
confidence: 98%
“…Premature cardiovascular disease (CVD) is the leading cause of death in patients with kidney disease (CKD) [[1], [2], [3]], which is only partially explained by the effects of traditional CV risk factors and atherothrombotic coronary vascular complications. The non-atherosclerotic myocardial processes, which are intrinsically linked to marked structural and functional abnormalities include profound hypertrophic and interstitial remodeling and deposition of myocardial fibrosis [1], often referred to as ‘uremic cardiomyopathy’ [2]. Progression of CKD is associated with marked increase of risk of adverse events, including arrhythmia, sudden cardiac death and heart failure (HF) [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the glomerular filtration rate (GFR) test, CKD is classified into five stages and patients with CKD in the 5th stage, which is also known as end‐stage‐kidney‐disease (ESKD), may need kidney replacement therapy . The continued development of CKD results in the increased risk of cardiovascular (CV) disease and may even lead to sudden cardiac death and heart failure . The major challenge of the CKD treatment is that there were no early clinical symptoms before CKD develops to the irreversible damage phase .…”
Section: Introductionmentioning
confidence: 99%
“… 6 Evidence from echocardiography and cardiac magnetic resonance (CMR) imaging studies suggests that adverse cardiac structural and functional change in CKD including elevated left ventricular (LV) mass begins early in CKD. 7 9 …”
mentioning
confidence: 99%